SAGAR (Security and Growth for All in the Region) and IPOI (Indo-Pacific Oceans Initiative): Shaping India's Security Through Regional Development - A. V. Kupriyanov (Сравнительная политика, 2022)
The world system is undergoing a period of transformation and refragmentation, the disintegration of a single political space into spheres of infl uence formed by the great powers. India, which forms such a sphere around itself, is faced with the problem: a serious economic and military lag behind China, trying, following the ideasof the Indian elites, to achieve hegemony in Southeast and South Asia and the Indian Ocean region. To fend off these attempts, India has put forward two concepts: Security and Growth for All in the Region (SAGAR) and the Indo-Pacifi c Oceans Initiative (IPOI). The article is devoted to the analysis of the problems that New Delhi is trying to solve with the help of these concepts, and the consideration of the very process of their implementation. The author notes that both SAGAR and IPOI are not developed strategic documents, but a type of ‘vision’ typical for Indian foreign policy discourse. At the same time, the active assistance provided by India to the countries of the Indian Ocean region within the framework of SAGAR demonstrates that Indiaperceives these countries as part of its sphere of infl uence and is trying to tie them to itself both politically and economically. On the contrary, the concept of ITOI aims to form partnerships and informal alliances with ASEAN countries and Australia. The author believes that Indian regional concepts are of interest to Russia, allowing it to use the Indian experience and to participate in Indian initiatives.